2012
DOI: 10.1111/j.1600-0536.2012.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing with own cosmetics—a prospective study of testing and reporting of adverse effects to the Swedish Medical Products Agency

Abstract: For a substantial number of patients, their own cosmetics were suspected of causing adverse reactions and were therefore tested. During the study, the number of reports to the MPA tripled, and the relevant products were easier to identify.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The reported adverse events in a study conducted in Ethiopia were allergic reactions (36%), acne (16%), and skin thinning (9.6%) [ 14 ]. Another study reported events such as itching (68.9%), redness (61%), acne (14.2%), and scaling of hair (19.3%) by frequent use of products classified as cosmetics [ 25 ]. Factors such as seasonal variations, hormonal imbalance, bacterial, parasite, and fungal infection, and psychological issues such as stress and unhygienic practices can be responsible for ACRs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported adverse events in a study conducted in Ethiopia were allergic reactions (36%), acne (16%), and skin thinning (9.6%) [ 14 ]. Another study reported events such as itching (68.9%), redness (61%), acne (14.2%), and scaling of hair (19.3%) by frequent use of products classified as cosmetics [ 25 ]. Factors such as seasonal variations, hormonal imbalance, bacterial, parasite, and fungal infection, and psychological issues such as stress and unhygienic practices can be responsible for ACRs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…National platforms dedicated to the reporting of adverse reactions are essential to better collect vigilance data [4]. Further efforts should be made to facilitate the report of reactions related to the use of dermo-cosmetic products by physicians and consumers [27,32,33]. Pierre Fabre Laboratories regularly hold sessions of information for health care professionals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Los documentos que se seleccionaron para el estudio fueron clasificados según el tipo de información que contenían como: "normatividad", "artículo científico", "fichas de notificación", "guías o manuales", "trabajos de grado" y otra categoría que incluía "varios", en donde se encuentran por ejemplo, relatorías y simposios acerca de normatividad. ) ha publicado artículos científicos sobre la realización de estudios piloto de un sistema de cosmetovigilancia con el objetivo de monitorear el riesgo de ocurrencia de efectos graves no deseados atribuibles a cosméticos, incluyendo la presentación de informes y el registro sistemático de esos efectos, seguido por el análisis y la evaluación de los datos [7,[55][56][57][58]. Estos estudios demuestran que a pesar que las regulaciones afirman que los productos cosméticos deben ser seguros, estos productos pueden causar efectos graves no deseados y además, que sólo un pequeño porcentaje de los consumidores que presentan un efecto grave no deseado, informan a un profesional de la salud [32,55,56].…”
Section: Descripción De La Documentación Encontradaunclassified